Why do Zakah Institutions in Sri Lanka Underperform? - Mohammed Arafath Careem Mohammed Jiffry; Abdulhamid Mohammed Ali Zaroum; Muhammad Amanullah; Ataollah Rahmani (Journal of Islamic Economics and Finance Studies, 2023)
Zakah as a compulsory worship obligation of Muslims has been practiced for several decades in an institutionalized form in Sri Lanka. Although the institutionalized mechanism contributes to some improvements in socioeconomic conditions, recent research highlighted that the impact of such a model is yet below the expected level. The institutional zakah practice in Sri Lanka has remained essentially informal lacking any state recognition or zakah specific regulation. This paper examined the contemporary challenges and root causes of the zakah institutions’ underperformance in Sri Lanka. This paper took a qualitative methodology and collected primary and secondary data through official documents, interviews, and published literature. The empirical findings of the paper reveal a threefold challenge that contributes to the inefficient institutional zakah performance, namely low collection, ineffective disbursement, and external hurdles. The paper suggests that the prolonged dominant informal and individualist zakah culture of Sri Lankan Muslims fails to actualize the designated goals of zakah and this in turn has contributed to the contemporary challenges. The paper highlights the need for developing an alternative jurisprudential methodology that has the potential to offer sensible remedies to the contemporary identified challenges. The paper suggests that zakah institutions must thoroughly re-evaluate existing zakah applications to improve the effectiveness and efficiency of their zakah management systems. It is also suggested that it would be helpful to establish a National Zakah Consultative Body that can advise the government on adopting effective regulations or guidance relevant to zakah management for the Sri Lankan Muslim minority.